Preventing Internalizing Problems in 6–8 Year Old Children: A Universal School-Based Program - Pophillat, Eugenie; Rooney, Rosanna M.; Nesa, Monique; Davis, Melissa C.; Baughman, Natalie; Hassan, Sharinaz; Kane, Robert T. (Frontiers in Psychology, 2016)
The Aussie Optimism Program: Feelings and Friends (AOP-FF) is a 10 week, universal mental health promotion program based on social/emotional and cognitive and behavioural strategies. The aim of the current study was to evaluate the efficacy of a universal Cognitive Behavioural Therapy based program in preventing and reducing internalising problems in six to eight year olds (Years 1-3 in Australia). Year 1-3 students from a low SES primary school (N = 206) were randomly assigned in classes to either an intervention or a control group and assessed at baseline and post-test. Results showed a significant (p = .009) and small to moderate (partial eta-squared = .034) pre-post decrease in parent-reported anxiety symptoms for the intervention group, in conjunction with a non-significant (p = .708) and negligible (partial eta-squared = .001) pre-post increase for the control group. A larger randomised controlled trial assessing longer term effects is needed. In addition the program needs to be simplified for year 1-2 students with a separate more developmentally appropriate program for year 3 students.